Hubungan Pola Asuh Orangtua Terhadap Tumbuh Kembang Anak Dan Kejadian Obesitas Di Sekolah Dasar Swasta Bruder Melati Pontianak - Puspita, Dinarwulan; Makmuriana, Lestari; Mariani, Agustina Rita (Jurnal Keperawatan dan Kesehatan, 2014)
Background: Parenting parents playes an important role in the growth process of children and the incidence of obesity this is increased in Indonesia. Due to various factors incidence one of them hereditary, lifestyle, use less calories and increasing economic status. Objectives: To examined the relationship parenting parents toward child development and the incidence of obesity in school-aged children at Bruder Melati Elementary School Pontianak. Methods: The design used in this study was a retrospective observational study with a cross sectional used random sampling technique, obtained a population of 41 respondents with a sample of 37 respondents were parents of children with obesity. Results: This study got that were relation parenting parents between development of the child (0.001 < 0.05), no relation parenting parents between incidence of obesity (0.402 < 0.05 ), there were relationship hereditary factors between incidence of obesity in children (0.012 < 0.05), that relation uses less calories between incidence of obesity in children (0.001 < 0.05), there were relation lifestyle between incidence of obesity (0.000 < 0.05), there were relation economic status between incidence of obesity (0.013 < 0.05). Conclusion: There is relationship between parents care to obesity experience